Sensilla Morphology and Complex Expression Pattern of Odorant Binding Proteins in the Vetch Aphid Megoura viciae (Hemiptera: Aphididae) - Bruno, Daniele; Grossi, Gerarda; Salvia, Rosanna; Scala, Andrea; Farina, Donatella; Grimaldi, Annalisa; Zhou, Jing-Jiang; Bufo, Sabino A.; Vogel, Heiko; Grosse-Wilde, Ewald; Hansson, Bill S.; Falabella, Patrizia (Frontiers in Physiology, 2018)
Chemoreception in insects is mediated by several components interacting at different levels and including odorant-binding proteins (OBPs). Although recent papers demonstrate that the function of OBPs cannot be restricted to an exclusively olfactory role, and that OBPs have been found also in organs generally not related to chemoreception, their feature of binding molecules remains undisputed. Studying the vetch aphid Megoura viciae (Buckton), we used a transcriptomic approach to identify ten OBPs in the antennae and we examined the ultrastructural morphology of sensilla and their distribution on the antennae, legs, mouthparts and cauda of wingless and winged adults by scanning electron microscopy (SEM). Three types of sensilla, trichoid, coeloconic and placoid, differently localized and distributed on antennae, mouthparts, legs and cauda, were described. The expression analysis of the ten OBPs was performed by RT-qPCR in the antennae and other body parts of the wingless adults and at different developmental stages and morphs. Five of the ten OBPs (MvicOBP1, MvicOBP3, MvicOBP6, MvicOBP7 and MvicOBP8), whose antibodies were already available, were selected for experiments of whole-mount immunolocalization on antennae, mouthparts, cornicles and cauda of adult aphids. Most of the ten OBPs were more expressed in antennae than in other body parts; MvicOBP1, MvicOBP3, MvicOBP6, MvicOBP7 were also immunolocalized in the sensilla on the antennae, suggesting a possible involvement of these proteins in chemoreception. MvicOBP6, MvicOBP7, MvicOBP8, MvicOBP9 were highly expressed in the heads and three of them (MvicOBP6, MvicOBP7, MvicOBP8) were immunolocalized in the sensilla on the mouthparts, supporting the hypothesis that also mouthparts may be involved in chemoreception. MvicOBP2, MvicOBP3, MvicOBP5, MvicOBP8 were highly expressed in the cornicles-cauda and two of them (MvicOBP3, MvicOBP8) were immunolocalized in cornicles and in cauda, suggesting a possible new function not related to chemoreception. Moreover, the response of M. viciae to different components of the alarm pheromone was assessed by behavioral assays on wingless adult morph; (-)-α-pinene and (+)-limonene were found to be the components mainly eliciting an alarm response. Taken together, our results represent a road map for subsequent in-depth analyses of the OBPs involved in several physiological functions in M. viciae, including chemoreception.